Service Quality of maternity care from the perspective of pregnant women in Tabriz Health Centers and Health Posts - 2010-2011 - J.S Tabrizi; K Gholipour; R Alipour; M Farahbakhsh; M Asghari-Jafarabadi; M Haghaei (Tehran University of Medical Sciences, 2014)
Objective: This study was aimed to assess Service Quality (SQ) of maternity care from the perception of pregnant women. Methods and materials: A cross-sectional study was conducted using a sample of 185 pregnant women at the 9th month of pregnancy were selected randomly from 40 health posts and urban health centers in Tabriz, Iran. Service Quality was calculated using: SQ = 10 - (Importance × Performance) based on importance and performance of non-health aspects from the customer' perspective. Data collection used a researcher-developed questionnaire whose validity and reliability was reviewed and confirmed. Data analyzed using SPSS-17 software. Independent sample T-test and ANOVA were used to investigate relationship between service quality dimensions and categorical variables. Results: From the customers' perspective the average service quality score was 7.59 of 10. Service quality aspects of "confidentiality" achieved scores at the level of good quality (≥9) and "support group" (3.48) reached low service quality scores. Also, result indicate housewife assess SQ better than worker (p=0.047) and mother who's have planned pregnancy has had greater SQ score (p=0.022). Although, in the linear regression analysis, job status and planned pregnancy were significantly and independently related to SQ score. Conclusion: Findings revealed a significant room for quality improvement in most aspects of provided care, particularly support group and safety from the perception of people who received maternity care.